Purine enzyme activities in recent onset rheumatoid arthritis: are there differences between patients and healthy controls? - Stolk, J N (1996)
OBJECTIVE: Purine enzyme activities may predict the effectiveness of azathioprine treatment and be associated with increased deaths from infectious diseases. In rheumatoid arthritis, patients show variable responses to azathioprine and a higher percentage of death is caused by infections. The aim of the study was to investigate possible rheumatoid arthritis associated abnormalities of purine enzyme activities by measuring several of these enzymes in patients with recent onset rheumatoid arthritis before treatment with disease modifying antirheumatic drugs or prednisone. METHODS: 23 patients with recent onset rheumatoid arthritis and 28 healthy controls were studied. Activities of the enzymes 5'-nucleotidase, purine nucleoside phosphorylase (PNP), hypoxanthine guanine phosphoribosyltransferase (HGPRT), and thiopurine methyltransferase (TPMT) were measured. Assessment of disease activity and blood sampling for routine measurements and HLA typing were done simultaneously. RESULTS: Purine enzyme activities did not differ between patients and healthy controls. Enzyme activities had no significant relations with indices of disease activity or rheumatoid factor titre or with the rheumatoid arthritis associated HLA types. Activity of 5'nucleotidase decreased with age (P < or = 0.05) and was lower by about 27% (P = 0.007) in males than in females. CONCLUSIONS: In rheumatoid arthritis patients, neither the variability in azathioprine effectiveness nor the increased death rate from infections can be explained by pre-existing abnormalities in the activities of the purine enzymes 5'-nucleotidase, PNP, HGPRT, or TPMT at an early stage of the disease, before disease modifying antirheumatic drugs or prednisone treatment. Besides adjustment for age, results of studies involving purine 5' nucleotidase activity should also be adjusted for sex.